Climatology of thunderstorm activity over the Indian region : II. Spatial distribution (MAUSAM, 2004)
Thunderstorms play important roles in many areas of information about earth-atmosphere relationship.  Inspite of this awareness of importance of thunderstorms, it is noted that studies about thunderstorms over India received little attention in the past.  Latest (IMD, 1999) climatological monthly data of number of thunderstorm days (Thn), rainy days (Tnr), and rainfall amount (Trr) for 276 Indian observatory stations are analyzed, over 11 geographic regions comprising India, to examine relationship between these parameters.  Analysis of Thn and Tnr data sets showed that in the premonsoon season major part of India is strongly dominated by frequent and widespread thunderstorms but with occasional rainy days.  However, in the monsoon season on account of very large increase in the rainy days over the thunderstorm days, the Thn-Tnr relationship is reversed.  The climatological feature of India in the premonsoon season is noted as a characteristic of cumulonimbus regime of continental convection, and the one in the monsoon season is termed as cumulonimbus regime of monsoonsal convection.  The prominence of monsoonal convective regime is therefore very important in deciding the performance of Indian southwest monsoon.  The analysis between Trr and Thn was carried out over 11 geographic regions of India in the four seasons of the annual period.  Results pertaining to monsoon season showed that the contribution of thunderstorms to rainfall is highest among the other three seasons. It is inferred that thunderstorm’s rain contribution to monsoonal rainfall is significant.